On Tremolo and Guitar Tremolo: A Study of Two Original Works, Cinéticas de Io and Escritos no Pó (Orfeu, 2025)
This article investigates the tremolo technique on the guitar, considering its theoretical, compositional, and performance-related implications. The study is based on the analysis of two original works—Escritos no Pó (2023), for guitar and electronics, and Cinéticas de Io (2024), for eight-string guitar. It begins by addressing the concept of tremolo in music theory and its practical variations across different instrumental families, highlighting its value as a timbral resource and as a solution to certain instruments’ technical limitations, such as sustaining long notes. The discussion then turns to the guitar-specific technique, presenting it as possessing broad expressive potential, capable of producing complex textures and expanding the instrument’s polyphonic possibilities. Finally, the analysis of the works demonstrates the role of tremolo as a unifying and structuring element in the compositional process, while also suggesting new directions for its exploration in contemporary music. This study aims to contribute to guitarists, composers, and researchers by offering an integrative approach that bridges practice and theory.
Keywords: tremolo; guitar; musical composition